Dampak pengembangan ekonomi lokal terhadap kemandirian masyarakat kampung Batik Laweyan - Rahmahanani Puspita; Hana Indriana (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
Kampung Batik Laweyan is one of the oldest Batik Villages in Indonesia and is an integrated tourism area. It not only focuses on batik trading, but also batik education, historical tourism, and regional culinary specialties. Kampung Batik Laweyan is a manifestation of an inclusive economy for the community. The activities of the Kampung Batik Laweyan community utilize local economic potential with the aim of community independence and welfare. The purpose of this study is to analyze the impact of local economic development on community independence in Kampung Batik Laweyan. This study used a quantitative approach with a questionnaire supported by a qualitative approach with in-depth interviews. The sampling technique used simple random sampling with a total of 35 respondents. The data were processed with the Spearman Rank correlation test to determine the correlation of local economic development with community self-reliance and SEM PLS regression test to determine the impact of local economic development on community self-reliance. Thus, human capital development and financial support need to be improved so the local economic development process can carry out massively and have impacts on the welfare of local communities. Policies that focus on education and access to financial resources will ensure broader and sustainable impact. The results showed a correlation between the level of local economic development and the level of community independence. The higher the value of local economic development, the higher the value of community independence. Local economic development affects community self-reliance in the aspects of human capital and financial capital.